Arduino step by step 2017 : getting started - Dalmaris, Peter (Packt Publishing, 2017)
"This course is for the new Arduino Maker. In making this course, I emphasized the importance of getting the basics right and learning to mastery. As an educator for over 15 years, I know first-hand that hitting a roadblock because you lack the fundamental knowledge to progress can be demotivating. Apart from knowing how to use the components that I demonstrate in this course, you will also learn how to read datasheets, how to use libraries on your own, and how to learn the skills you need to create the gadgets you want, on your own. With knowledge comes freedom, and I will help you get there. I invite you to review the free lectures in the first section of the course to find out more details about it. If you are excited about becoming a Maker with the Arduino, join many other Makers and me in Arduino Step by Step 2017: Getting Started!"--Resource description page